GE_GERICHTE C/4364/2016 vom 7. Juli 2016 - GE Cour de justice (2016)
POURSUITE PAR VOIE DE FAILLITE ; AJOURNEMENT DE LA FAILLITE ; SURENDETTEMENT | LP.174.2; LP.173a.2; LP.192; LP.190.1.2; Cst.29.2; CO.725a;